SARS-CoV-2: Pathogenesis, Molecular Targets and Experimental Models - Kanimozhi, G.; Pradhapsingh, B.; Singh Pawar, Charan; Khan, Haseeb A.; Alrokayan, Salman H.; Prasad, N. Rajendra (Frontiers in Pharmacology, 2021)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a recent pandemic outbreak threatening human beings worldwide. This novel coronavirus disease-19 (COVID-19) infection causes severe morbidity and mortality and rapidly spreading across the countries. Therefore, there is an urgent need for basic fundamental research to understand the pathogenesis and druggable molecular targets of this organism. Recent, sequencing data of the viral genome and X-ray crystallographic data of the viral proteins illustrate potential molecular targets to be investigated for structure-based drug design. Further, the SARS-CoV-2 viral pathogen isolated from clinical samples needs to be cultivated and titrated. All of these scenarios demand suitable laboratory experimental models. The experimental models should mimic the viral life cycle as it happens in the human lung epithelial cells. Recently, researchers employing primary human lung epithelial cells, intestinal epithelial cells, experimental cell lines like Vero cells, CaCo-2 cells, HEK-293, H1299, Calu-3 for understanding viral titer values. The human iPSC derived lung organoids, small intestinal organoids, and blood vessel organoids gain increasing interest among researchers to understand SARS-CoV-2 biology and treatment outcome. The SARS-CoV-2 enters the human lung epithelial cells using viral Spike (S1) protein and human angiotensin-converting enzyme 2 (ACE-2) receptor. The laboratory mouse show poor ACE-2 expression and thereby inefficient SARS-CoV-2 infection. Therefore, there was an urgent need for developing transgenic hACE-2 mouse models for understanding the therapeutic outcome of antiviral agents. In this review, we highlighted the viral pathogenesis, potential druggable molecular targets, and suitable experimental models for basic fundamental research.